WALL PAINTING OF THE 17th ‒ 18th CENTURY IN THE CHURCH OF SAINT ARCHISTRAG MICHAEL IN THE VILLAGE OF KRAYNYKOVO IN TRANSCARPATIA: A SYNTHESIS OF POST-BYZANTINE AND UKRAINIAN FOLK TRADITIONS - Нестеренко, Андрій Олександрович (Art and Design, 2024)
The purpose of the article is to carry out a stylistic analysis of the wall paintings of the 17th - 18th centuries in the church of St. Michael the Archangel in the village of Kraynikovo in Transcarpathia and to identify the characteristic features of the processes that took place in church painting during this period in this region of Ukraine. The principles and methods of the article are determined by the set aim. The work is based on the scientific principles of systematicity and historicism. The research used both general scientific research methods (analysis and synthesis, induction and deduction, systematization and generalization, abstraction, typology), and special art studies methods (artistic-stylistic, historical-cultural and comparative methods for comparing different artistic phenomena and means of expression, individual images). The article analyzes preserved wall paintings of the 17th – 18th centuries in the church of St. Michael the Archangel in the village of Kraynikovo in Transcarpathia. A comparison with the iconographic programs of wall paintings of the same historical period in wooden churches of the border villages of Romania – Budeshti Josani, Oncesti and Ieudi, as well as with similar paintings in churches in Drohobych and Potelych in the Lviv region was made. The mutual influences that took place in the sacral painting of Transcarpathia and the borderlands of Romania, part of whose territory in the 17th and 18th centuries were part of the Marmara County (Marmara County), Halychyna, and Kyiv, were established. An original synthesis of post-Byzantine traditions with icon-painting programs of folk masters in the village of Kraynikovo in Transcarpathia was revealed. For the first time in Ukrainian art history, an analysis of wall paintings of the 17th - 18th centuries in the church of St. Archangel Michael in the village of Kraynikovo in Transcarpathia was carried out, the originality of the iconographic program of painting was revealed, and connections with the iconography of the paintings of wooden churches in the border villages of Romania and Galicia were traced. On the basis of the conducted research, the regional peculiarities of the processes that took place in church painting in Transcarpathia during the studied period were determined. The results of this study can be used: in general works on the history of Ukrainian art; in the preparation of scientific monographs, textbooks, teaching aids, methodological developments, educational and professional programs; in the lecture materials of teachers in educational and art institutions, as well as during the restoration work on the preservation of wall paintings in the church of St. Archangel Michael in the village of Kraynikovo in Transcarpathia, as a unique national heritage in the artistic culture of Ukraine.